Accounting information quality, governance efficiency and capital investment choice - Jinbu Zhai; Yutao Wang (China Journal of Accounting Research, 2016)
This paper examines the relationship between accounting information quality and capital investment choice from the perspective of accounting information's governance function. Measuring capital investment choice as the correlation of growth of operating income between company and industry, this paper investigates whether and to what extent companies focus on their core business. The results show that the higher the quality of publicly listed firms' accounting information, the stronger that correlation, particularly when the corporate governance of the listed company is poor. The findings imply that accounting information quality can thus optimize the capital investment choice, which complements and strengthens the functioning of corporate governance. Hence, regulators should pay more attention to the market's power to supervise the behavior of listed firms, improve the governance functions of accounting information and increase the efficiency of capital allocation.
Keywords: 650; Accounting information quality; Governance efficiency; Capital investment choice